Mechanism of Action of Acupuncture in Obesity: A Perspective From the Hypothalamus - Wang, Li; Yu, Chao-Chao; Li, Jia; Tian, Qing; Du, Yan-Jun (Frontiers in Endocrinology, 2021)
Obesity is a prevalent metabolic disease caused by an imbalance in food intake and energy expenditure. Although acupuncture is widely used in the treatment of obesity in a clinical setting, its mechanism has not been adequately elucidated. As the key pivot of appetite signals, the hypothalamus receives afferent and efferent signals from the brainstem and peripheral tissue, leading to the formation of a complex appetite regulation circuit, thereby effectively regulating food intake and energy homeostasis. This review mainly discusses the relationship between the hypothalamic nuclei, related neuropeptides, brainstem, peripheral signals, and obesity, as well as mechanisms of acupuncture on obesity from the perspective of the hypothalamus, exploring the current evidence and therapeutic targets for mechanism of action of acupuncture in obesity.